1996
DOI: 10.1046/j.1365-2141.1996.d01-1946.x
|View full text |Cite
|
Sign up to set email alerts
|

TEL‐AML1 fusion in acute lymphoblastic leukaemia of adults

Abstract: A number of fusion genes have been identified by study of acquired chromosomal translocations. Their detailed characterization has provided insights into mechanisms of leukaemogenesis and has enabled the development of molecular methods to assist in the diagnosis and monitoring of residual disease after treatment. The TEL-AML1 fusion gene is associated with a cryptic t(12:21)(p12:q22) translocation, and is the commonest known genetic abnormality in childhood B-cell precursor acute lymphoblastic leukaemia (ALL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 0 publications
2
35
0
1
Order By: Relevance
“…Although originally identi®ed by its fusion to the plateletderived growth factor receptor b (PDGFR-b) gene in chronic myelomonocytic leukemia accompanied by the t(5;12) (Golub et al, 1994), the TEL gene (also called ETV6) has also been found fused to the MN1 gene , the ABL gene (Papadopoulos et al, 1995), the JAK2 gene (Peeters et al, 1997a), the EVI-1 gene (Peeters et al, 1997b) and the AML1 gene (Golub et al, 1995;Romana et al, 1995a). The most common of these fusions is TEL-AML1, which is encoded by a t(12;21) translocation and is found in up to 25% cases of childhood B-lineage acute lymphoblastic leukemia (ALL) (Romana et al, 1995b;Shurtle et al, 1995), but only rarely in adult ALL (Aguiar et al, 1996;Raynaud et al, 1996;Shih et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Although originally identi®ed by its fusion to the plateletderived growth factor receptor b (PDGFR-b) gene in chronic myelomonocytic leukemia accompanied by the t(5;12) (Golub et al, 1994), the TEL gene (also called ETV6) has also been found fused to the MN1 gene , the ABL gene (Papadopoulos et al, 1995), the JAK2 gene (Peeters et al, 1997a), the EVI-1 gene (Peeters et al, 1997b) and the AML1 gene (Golub et al, 1995;Romana et al, 1995a). The most common of these fusions is TEL-AML1, which is encoded by a t(12;21) translocation and is found in up to 25% cases of childhood B-lineage acute lymphoblastic leukemia (ALL) (Romana et al, 1995b;Shurtle et al, 1995), but only rarely in adult ALL (Aguiar et al, 1996;Raynaud et al, 1996;Shih et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Among nine studies of ETV6/AML1 in adult ALL, five have reported incidences of 3.2%, 1 0.8%, 2 3%, 3 3.3% 4 and 4.4%, 5 while four (including Cuneo et al) have failed to identify any cases with the fusion. [6][7][8] In our continuing interphase FISH screening program we have now examined a total of 307 unselected and consecutive de novo adult patients with ALL and have found a total of eight to be positive for the ETV6/AML1 fusion.…”
Section: To the Editormentioning
confidence: 99%
“…30 We detected the TEL-AML1 fusion transcript in 22% of randomly selected childhood ALL cases, confirming its high frequency at diagnosis. 4 The fusion transcript has also been detected in adult ALL, albeit at frequencies of only 0-3.4% 11,30,[40][41][42] and only in adults less than 28 years old. 41,42 It is rarely detected in cases of infant ALL 43 or in ALL patients with Down syndrome.…”
Section: 29mentioning
confidence: 99%